2019
DOI: 10.1088/1742-6596/1315/1/012069
|View full text |Cite
|
Sign up to set email alerts
|

An analysis to student error of algebraic problem solving based on polya and newman theory

Abstract: This study aims to reveal student algebraic problem-solving errors based on Polya and Newman hierarchical indicator. The subject was a study of 30 students of grade VII in one of the junior high school located in the Timor Tengah Utara, NTT, Indonesian, 2018/2019 period. Process of collecting data used tests and interviews. The result of the student problem-solving ability test was grouped into three parts, namely 5 of the student in the low category, 20 of the student in the medium category, and 5 of students… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
9
0
6

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 19 publications
(15 citation statements)
references
References 3 publications
0
9
0
6
Order By: Relevance
“…Difficulties in solving mathematical problems are also experienced by seventh-grade students of Junior High School in North Central Timor Regency, located in the border areas between the Republic of Indonesia and the Democratic Republic of Timor Leste. This is proven through the results of research by Son, Darhim, and Fatimah (2019) about errors made in solving algebraic problems based on Polya's and Newman's theory. The results showed that more than 50% of the participants made errors in solving algebra problems.…”
mentioning
confidence: 96%
“…Difficulties in solving mathematical problems are also experienced by seventh-grade students of Junior High School in North Central Timor Regency, located in the border areas between the Republic of Indonesia and the Democratic Republic of Timor Leste. This is proven through the results of research by Son, Darhim, and Fatimah (2019) about errors made in solving algebraic problems based on Polya's and Newman's theory. The results showed that more than 50% of the participants made errors in solving algebra problems.…”
mentioning
confidence: 96%
“…Metode umum digunakan untuk menganalisis jawaban siswa yang mengalami kesalahan adalah Prosedur Newman dan Polya (Son et al, 2019). Prosedur Polya terdiri dari 4 tahapan, yaitu memahami masalah, menyusun rencana pemecahan, melaksanakan rencana, dan memeriksa kembali.…”
Section: Pendahuluanunclassified
“…Hasil tersebut menunjukkan bahwa kesalahan siswa berdasarkan analisis kesalahan Newman sering terjadi pada tahap keterampilan membaca, pemahaman dan proses. Son et al (2019) Penelitian tersebut merupakan penelitian yang dilakukan pada tingkat sekolah menengah atas dan pertama. Masih jarang analisis kesalahan yang dilakukan di perguruan tinggi.…”
Section: Pendahuluanunclassified